A review of process intensified CO2 capture in RPB for sustainability and contribution to industrial net zero - Shukla, Chetna; Mishra, Poonam; Dash, Sukanta Kumar (Frontiers in Energy Research, 2023)
Carbon dioxide (CO2), a significant greenhouse gas released from power plants and industries, substantially impacts climate change; minimizing it and achieving carbon net zero is essential globally. In the direction of reducing CO2 emissions into the atmosphere, post-combustion carbon capture from the large point CO2 emitters by chemical absorption involving absorption of this gas in a capturing fluid is marked as that of a commonly used and efficacious mechanism. Researchers have worked on the process using conventional columns. But process intensification technology is required because of the high capital cost, the absorption column height, and the traditional columns' low energy efficiency. Rotating Packed Bed (RPB) process intensified equipment has been identified as a suitable technology for enhanced carbon capture using an absorbing fluid. This paper reviews and discusses recent model developments in the post-combustion CO2 capture process intensification using RPBs. In literature, various workers have developed steady-state mathematical models about mass balance and energy balance equations in gas and liquid phase using ordinary or partial differential equations. Due to the circular shape, equations are considered in a radial direction and have been solved using a numerical approach and simulated using different software platforms, viz. MATLAB, FORTRAN, and gPROMS. A comparison of various correlations has been presented. The models predict the mole fraction of absorbed CO2 and correspond well with the experimental results. Along with these modeling, experimental data review on RPB is also included in this work.